1997
DOI: 10.1007/s000400050028
|View full text |Cite
|
Sign up to set email alerts
|

Colony foraging in different species of stingless bees (Apidae, Meliponinae) and the regulation of individual nectar foraging

Abstract: For Melipona fasciata, M. beecheii, M. favosa and Tetragonisca angustula we found distinct intergeneric differences in foraging activity patterns. The Melipona species had a longer daily foraging activity period than T. angustula. Pollen foraging patterns of the Melipona species were different from that of T. angustula: Melipona collect pollen earlier in the day. In an experimental habitat without competitors, Melipona favosa did not collect pollen very early in the day.Individually marked returning foragers d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 18 publications
2
41
0
8
Order By: Relevance
“…Some authors demonstrated the same pattern for the genus Melipona (Sommeijer et al, 1983;Biesmeijer, 1997;Bruijn and Sommeijer, 1997;Cortopassi-Laurino, 2004). Pollen peaks in the morning are related to a greater availability of the resource at this time and, consequently, to competition with other bees for this limited resource (Roubik, 1989).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Some authors demonstrated the same pattern for the genus Melipona (Sommeijer et al, 1983;Biesmeijer, 1997;Bruijn and Sommeijer, 1997;Cortopassi-Laurino, 2004). Pollen peaks in the morning are related to a greater availability of the resource at this time and, consequently, to competition with other bees for this limited resource (Roubik, 1989).…”
Section: Introductionmentioning
confidence: 78%
“…Heard and Hendrikz (1993) affirm that temperature and light intensity are the main factors that affect flight activity of Trigona carbonaria in Australia, initially imposing limits outside of which external activity ceases and, later, within these limits correlating with this activity. Some authors have reported that peaks of pollen collection for the genus Melipona occurred at the beginning of the morning and that of nectar at the end of the morning and in the afternoon, considering it as a standard behavioral pattern for the genus (Sommeijer et al, 1983;Roubik and Buchmann, 1984;Bruijn et al, 1991;Bruijn and Sommeijer, 1997;Biesmeijer, 1997;Pierrot and Schlindwein, 2003). However, for Melipona rufiventris, the two peaks were close, occurring between 6 hours and 9 hours.…”
Section: Discussionmentioning
confidence: 99%
“…A amplitude máxima diária de coleta de pólen foi de 10 horas correspondendo ao intervalo de tempo das atividades de coleta de néctar. BRUIJN & SOMMEIJER (1997) assinalaram uma divisão tempo- 2 -9 9 1 0 0 -1 9 9 2 0 0 -2 9 9 3 0 0 -3 9 9 4 0 0 -4 9 9 5 0 0 -5 9 9 6 0 0 -6 9 9 7 0 0 -7 9 9 8 0 0 -8 9 9 9 0 0 -9 9 9 1 0 0 0 -1 0 9 9…”
Section: Revista Brasileira De Zoologia 22 (3): 680-686 Setembro 2005unclassified
“…Changes in the microclimate of arboreal systems increase air humidity and decrease the temperature and wind speed with positive effects on insect development (Rao et al 2000). The quality of food resources may explain the greatest abundance of the bees, T. spinipes and T. angustula, on the east side of the canopy of A. mangium (Table 3) because leaves exposed to wind currents may present a higher evaporation, and thus increased nectar concentration in flowers (deBruijn & Sommeijer 1997).…”
Section: (1)mentioning
confidence: 99%